Investigation of the relationship between clinical severity of acne and inflammatory parameters in patients with acne vulgaris - Akca, Hanife Merve; Tuncer Kara, Kevser (Ondokuz Mayis Universitesi, 2023)
Objective In this study, we investigated whether the Neutrophil /Lymphosite (N/L) ratio, mean platelet volume (MPV) value, GADS (The global acne rating system) score and other inflammatory parameters are related in acne vulgaris patients. Methods One-hundred acne patients, aged between 18–40 years, who treated at the Karaman Training and Research Hospital Dermatology Polyclinic between January and March 2022 were included in the study. Age, sex, duration of disease, medications and additional systemic diseases were recorded. Acne patients included in the study were tested for N/L ratio, erythrocyte sedimentation rate (ESR, mm/hr), C-reactive protein (hsCRP, mg/L), platelet count (PLT/L) and (MPV/FL). GADS scores calculated. Results There was a significant difference in ESR (p < 0.001) and CRP levels (p = 0.002) in patients with high GADS scores compared to those with low GADS scores. In all patients, the mean GADS score was 24.77 ± 11.00, and GADS scores were positively correlated with ESR and CRP levels. In our binary logistic regression analysis of age, sex, time, N/L ratio, PLT/L, MPV and ESR for identifying risk factors for severe acne vulgaris, the model explained 25.7% of high GADS scores. A high CRP level was identified as a risk factor for having a high GADS score. Conclusion In our study, we evaluated acne patients because it affects many age groups, is common, and sometimes causes extensive inflammation. © 2023 Ondokuz Mayis Universitesi. All rights reserved.
Keywords: acne severity; acne vulgaris; inflammatory diseases; inflammatory parameters